2014
DOI: 10.14257/ijca.2014.7.8.18
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Testing and Fault Diagnosis of CNC Based on the Method of Cepstrum Identification

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Using the same method, Robles et al [9] obtained the effective localisation of cutting edges within the milling-head edge profile. Wu et al [10] identified dynamic characteristics and developed fault diagnosis method of a CNC machine, by using a spectrum analysis procedure of the milling-tool vibration signals. In addition, Zaghbany and Songmene [11] investigated the operational modal analysis (OMA) for dynamic modal parameter estimations, during machining operations.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same method, Robles et al [9] obtained the effective localisation of cutting edges within the milling-head edge profile. Wu et al [10] identified dynamic characteristics and developed fault diagnosis method of a CNC machine, by using a spectrum analysis procedure of the milling-tool vibration signals. In addition, Zaghbany and Songmene [11] investigated the operational modal analysis (OMA) for dynamic modal parameter estimations, during machining operations.…”
Section: Introductionmentioning
confidence: 99%